2019
DOI: 10.1096/fba.2019-00062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of several plasma proteins whose levels in colorectal cancer patients differ depending on outcome

Abstract: Colorectal cancer (CRC) stands for 10% of the worldwide cancer burden and has recently become the second most common cause of cancer death. The 5‐year survival rate depends mainly on stage at diagnosis. Mass spectrometric proteomic analysis is widely used to study the plasma proteome, which is complex and contains multitudes of proteins. In this study, we have used Ultra Performance Liquid Chromatography‐Ultra Definition Mass Spectrometry (UPLC‐UDMSE)‐based proteomics to analyze plasma samples from 76 CRC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…This data was confirmed by Western blot [218]. A high plasma level of MBP-C is a marker of poor survival for stage III CRC patients [171]. Using ELISA technique it was revealed that the MBP-C protein was significantly reduced in HCC cases [219].…”
Section: Mannose-binding Protein C (Mbl2_human)mentioning
confidence: 81%
See 3 more Smart Citations
“…This data was confirmed by Western blot [218]. A high plasma level of MBP-C is a marker of poor survival for stage III CRC patients [171]. Using ELISA technique it was revealed that the MBP-C protein was significantly reduced in HCC cases [219].…”
Section: Mannose-binding Protein C (Mbl2_human)mentioning
confidence: 81%
“…The higher level of fetuin-B in plasma is correlated with a favorable outcome in the case of CRC [171].…”
Section: Fetuin-b (Fetub_human)mentioning
confidence: 97%
See 2 more Smart Citations
“…However, recent studies show controversial results. Holm et al showed that high plasma levels of MBL2 are a marker of poor survival in colorectal cancer patients [ 117 ]. Yitting et al reported that the MBL complement activation pathway is activated in patients with colorectal cancer compared with healthy controls; however, MBL pathway deficiency rates are similar between patients and healthy controls [ 118 ].…”
Section: Discussionmentioning
confidence: 99%